Cutaneous Metastasis From Sacral Chordoma. (April 2017) - Gleghorn, Kristyna; Goodwin, Brandon; Sanchez, Ramon
Abstract : Abstract: Chordoma is a rare primary bone malignancy of notochord origin, representing 1-4% of malignant bone tumors.1, 2 Typically, chordomas follow a slow progressive course with aggressive local extension, multiple recurrences, and metastases.1 Of particular interest to this case, cutaneous metastasis is exceedingly rare. Diagnosis of this entity can be a challenge due to the rarity of chordoma, as well as the infrequent presentation of distant cutaneous metastasis and non-specific clinical skin findings. We report a case of a 61-year-old male with a history of sacral chordoma treated by wide local excision 8 years prior to presentation developed a nodule on his scalp for 6 weeks. Physical examination revealed a 1 cm rubbery, pink, shiny dome-shaped nodule on his left occipital scalp. Hematoxylin and eosin sections revealed a lobular dermal proliferation of small ovoid cells and larger physaliferous cells with hyperchromatic, displaced nuclei and finely vacuolated "soap-bubble" cytoplasm in a myxoid stroma. Immunohistochemistry of tumor cells showed positivity for both S-100 protein and pancytokeratin (AE1/AE3), while smooth muscle actin (SMA), P63, and CK7 were negative. Additionally, tumor cells stained positive for brachyury. The medical history, clinical presentation, histopathological appearance and immunohistochemical profile are consistent with cutaneous metastasis from sacral chordoma, known as chordoma cutis. This case illustrates the integral role of dermatopathology in the diagnosis of a rare and critical condition.